MODERN METHODS OF MITRAL VALVE PROLAPSE DIAGNOSTICS AND PREVALENCE ASSESSMENT IN YOUNG PEOPLE - E. G. Malev; S. V. Reeva; E. V. Timofeev; E. V. Zemtsovsky (Российский кардиологический журнал, 2010)
The paper presents echocardiography examination results in healthy young people. The prevalence of classic and nonclassic mitral valve prolapse (MVP) is assessed. The prevalence of primary myxomatous MVP is independent of gender or age, while non-classic MVP is more prevalent in younger individuals. The mitral valve morphology is compared to that observed in the Framingham Study. The potential of color Doppler M-ultrasound is assessed for late systolic mitral regurgitation diagnostics in MVP.